The effect of government decisions on the efficiency of the investment funds market in Poland - Witkowska, Dorota; Kompa, Krzysztof; Mentel, Grzegorz (Journal of Business Economics and Management, 2019)
Polish government introduced crucial changes concerning conditions of the pension funds functioning in the years 2011–2014. This article focuses on explaining the impact of these political decisions on efficiency of investment fund market in Poland. Therefore, the article aims (1) to find out if changing in functioning of pension funds also affected the efficiency of mutual funds which provide stable growth investment policy (i.e. similar investment strategy as pension funds) and (2) to check which type of investment funds, pension or mutual, were more efficient in the sense of returns and risks under new regulations. The analysis is provided for selected mutual funds using daily, weekly and monthly returns. The whole period of analysis, years 2009–2015, is divided into six sub-periods according to the three events, that essentially changed the functioning of the pension funds. Statistical tests for in pairs comparisons of returns and risks, and ratios for investment efficiency evaluation were applied. Findings show that pension funds performed better than mutual funds which are managed by the same company. More, the changes of the rules for pension funds’ functioning caused an increase of risk and a decrease of efficiency of the considered investment funds’ portfolios.